2000
DOI: 10.1021/bi001514d
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Rod Outer Segment Membrane Guanylate Cyclase Dimerization in A Cone−Rod Dystrophy Results in Defective Calcium Signaling

Abstract: Rod outer segment membrane guanylate cyclase1 (ROS-GC1) is the original member of the membrane guanylate cyclase subfamily whose distinctive feature is that it transduces diverse intracellularly generated Ca 2+ signals in the sensory neurons. In the vertebrate retinal neurons, ROS-GC1 is pivotal for the operations of phototransduction and, most likely, of the synaptic activity. The phototransduction-and the synapse-linked domains are separate, and they are located in the intracellular region of ROS-GC1. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 46 publications
(110 reference statements)
2
38
0
Order By: Relevance
“…A (62,63), we initially found that the "ERT" mutation linked to ad-CORD causes reduced catalytic activity when the mutant polypeptide is expressed alone. But our subsequent analyses of this and other adCORD mutants showed that the effect on intrinsic activity is not sufficient to explain the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…A (62,63), we initially found that the "ERT" mutation linked to ad-CORD causes reduced catalytic activity when the mutant polypeptide is expressed alone. But our subsequent analyses of this and other adCORD mutants showed that the effect on intrinsic activity is not sufficient to explain the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, disease causing mutations can also point to critical amino acid positions that determine structure-function relationships in natively folded protein structures and therefore might help to gain mechanistic insights of protein function and regulation (Duda et al, 1999a, 2000; Ramamurthy et al, 2001). For example, a biochemical study on mutations in the so-called dimerization domain of ROS-GC1 correlating with cone-rod dystrophy recently revealed that this dimerization or linker domain operates as a Ca 2 + -sensitive control switch module (Zägel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One example is ROS-GC1-E 786 D, R 787 C, T 788 M mutation. The mutation deranges the dimer formation of the guanylate cyclase and reduces the basal catalytic activity of the ROS-GC (Duda et al, 1999a, 2000; Tucker et al, 1999). This basic structural derangement in the guanylate cyclase, intriguingly, increases its sensitivity to GCAP1 and GCAP2.…”
Section: Ros-gc1 Gene Linked Retinal Dystrophiesmentioning
confidence: 99%